Improving Cadmium Resistance in Escherichia coli Through Continuous Genome Evolution - Qin, Weitong; Zhao, Jintong; Yu, Xiaoxia; Liu, Xiaoqing; Chu, Xiaoyu; Tian, Jian; Wu, Ningfeng (Frontiers in Microbiology, 2019)
Cadmium (Cd) is a heavy metal that is extremely toxic to many organisms; however, microbes are highly adaptable to extreme conditions, including heavy metal contamination. Bacteria can evolve in the natural environment, generating resistant strains that can be studied to understand heavy metal resistance mechanisms, but obtaining such adaptive strains usually takes a long time. In this study, the genome replication engineering-assisted continuous evolution (GREACE) method was used to accelerate the evolutionary rate of the Escherichia coli genome to screen for E. coli mutants with high resistance to cadmium. As a result, a mutant (8mM-CRAA) with a minimum inhibitory concentration (MIC) of 8 mM cadmium was generated, a value approximately 8-fold higher than that of the E. coli BL21(DE3) wild-type strain. Sequencing revealed 329 single nucleotide polymorphisms (SNPs) in the genome of the E. coli mutant 8mM-CRAA. These SNPs as well as RNA-Seq data on gene expression induced by cadmium were used to analyze the genes related to cadmium resistance. Overexpression, knockout and mutation of the htpX (which encodes an integral membrane heat-shock protein) and gor (which encodes glutathione reductase) genes revealed that these two genes contribute positively to cadmium resistance in E. coli. Therefore, in addition to the previously identified cadmium resistance genes zntA and capB, many other genes are also involved in bacterial cadmium resistance. This study assists us in understanding the mechanism of microbial cadmium resistance and facilitating the application of heavy-metal remediation.